Peasant woman from Huaro - Chira C., Carmen M. (1985)
Huaro, district of the province of Quispicanchis, in the department of Cusco, at 3,100 m.a.s.l. Its climate is temperate, due to its geographical location protected by the mountains. Its recognition as a district dates back to 1952, through Law 11363, in which the population centers of Pukuto, Phinay, Pujyupampa and Sullumayo are also indicated as its annexes. Before the date indicated Huaro was simply an annex of Urcos, capital of the province that is 3 kms. away. By belonging to Quispicanchis and due to the geographical and climatological conditions noted, this district integrates the "maize subregion within the Quechua zone, as classified by Glave, to which Urubamba, Urquillos, Calca, Cusco, Canchis, Paucartambo also belong ( red corn and jora), Limatambo, Paruro and Pampa de Anta (small corn)".